A Clinical Study to Evaluate the Efficacy of Mantra and Yantra Chikitsa on Sukhaprasava - Rangane, Arohi Sanjay; Vishala (International Research Journal of Ayurveda & Yoga, 2024)
Childbirth is the most powerful and beautiful experience in a women’s life. Although the experience of labor pain and childbirth is the most severe and agonizing events of her existence.Description of labor in Ayurvedic science, though found 500yrs ago is a very less known concept and not much in practice. Currently labor is managed with conventional medicines with some interventions of yoga and some Ayurvedic Preparations. This article focuses on one such practice used in Ayurveda for conduction of labor. Yantra and Mantra Chikitsa for Sukhaprasava is mentioned in our classics ,Observational clinical study was conducted to see the effect of Mantra and yantra Chikitsa on the progress of labor (in terms of bishop’s score, duration of labor, intensity of pain, operative and forceps delivery, fetal heart sound monitoring, healthy outcome of fetus, post partum complication).A total of 40 primi patients ; 20 in each groups where taken .Out of which 20 patients were given Chyavanmantra siddha jala and other 20 patients were given allopathic management for induction and augmentation of labor. As mentioned in the classics the use of Mantra (Chyavanmantra) showed positive outcome in the process and progress of labor. Keen observation was made and it concluded that Mantra and yantra Chikitsa given to patients in group A helped sukha and nirupadrava Prasava, by making cervix favorable, shortening duration of stages of labor and good fetal outcome also post-partum complication like post-partum hemorrhage, incidents of cervical tear where reduced.